Utilization of Microsoft Power Point Applications as Physics Learning Media Interactive On Diode Material - Abdin Abdin; Kasman Kasman; Asrun Safiuddin; La Ode Rusman (IKIP Mataram, 2023)
This study aims to provide new innovations in the use of Microsoft Power Point applications as interactive physics learning media on diode material. In addition, it motivates physics teachers to use technology in the implementation of learning in class. The target of this research is in the form of products resulting from the use of the Microsoft PowerPoint application as an interactive physics learning medium on diode material. This research method is research and development using a development model consisting of five stages, namely: (1) preliminary investigation; (2) design (3) realization/construction (realization/construction); (4) test, evaluation, and revision (test, evaluation, and revision); (5) implementation (implementation). The results of this study are the creation of interactive physics learning media through power point applications with the plomp model known as 5 stages, namely the initial investigation stage, design, realization/construction, test evaluation and revision and implementation. Power point interactive learning media is generally declared feasible to use after going through several trials carried out with material expert tests, media expert tests by looking at the results of the assessment of the two validators with a value obtained of 77.50 including the valid category for material experts and media experts obtaining a score of 78.46 is included in the valid category. It can also be seen that the effectiveness of learning media through the ability of student learning outcomes with a pretest score of 64.00 and a posttest score of 84.00 shows a significant increase in student learning outcomes.